2005
DOI: 10.1108/10610420510583743
|View full text |Cite
|
Sign up to set email alerts
|

Brand power revisited: measuring brand equity in cyber‐space

Abstract: Purpose -Cyber-brands are regularly valued but, to date, there has been no reported research designed to understand the derivation of cyber brands' equity, so that attempts can be made to increase their brands' equity efficiently. This research aims to address the issue. Design/methodology/approach -To measure the strength of cyber brands, prior off-line research is replicated, taking a customer focus to identify determinate variables. These customer-focused variables are tested against cyber consumers' stated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In the context of online shopping, research shows that experiential values could improve website personality (Shobeiri, Laroche, and Mazaheri 2013), preference for the e-retailer (Mathwick, Malhotra, and Rigdon 2001;Overby and Lee 2006), customer satisfaction (Lee and Overby 2004), emotions (Jeong et al 2009), website involvement (Shobeiri, Mazaheri, and Laroche 2014), attitudes toward the site/eretailer (Fiore, Kim, and Lee 2005;Keng and Ting 2009), customers' patronage intentions (Fiore, Kim, and Lee 2005;Jeong et al 2009;Mathwick, Malhotra, and Rigdon 2001;Soltani and Gharbi 2008), and the brand equity of dot-coms (Na andMarshall 2005, Page andLepkowska-white 2002). In these studies, experiential benefits are measured based on various proposed models in the literature including these of Schmitt (1999) (2001) is the only one that was originally developed for the context of online (as well as catalog-based) retailing.…”
Section: Experiential Dimensions Of E-shopping: a Cross-cultural Persmentioning
confidence: 98%
“…In the context of online shopping, research shows that experiential values could improve website personality (Shobeiri, Laroche, and Mazaheri 2013), preference for the e-retailer (Mathwick, Malhotra, and Rigdon 2001;Overby and Lee 2006), customer satisfaction (Lee and Overby 2004), emotions (Jeong et al 2009), website involvement (Shobeiri, Mazaheri, and Laroche 2014), attitudes toward the site/eretailer (Fiore, Kim, and Lee 2005;Keng and Ting 2009), customers' patronage intentions (Fiore, Kim, and Lee 2005;Jeong et al 2009;Mathwick, Malhotra, and Rigdon 2001;Soltani and Gharbi 2008), and the brand equity of dot-coms (Na andMarshall 2005, Page andLepkowska-white 2002). In these studies, experiential benefits are measured based on various proposed models in the literature including these of Schmitt (1999) (2001) is the only one that was originally developed for the context of online (as well as catalog-based) retailing.…”
Section: Experiential Dimensions Of E-shopping: a Cross-cultural Persmentioning
confidence: 98%
“…Na et al 2005 claimed and demonstrated brand equity was conceptually equal among any brands, and models of brand equity that work for off-line products and services would work well in an online context, too [2]. Herein, researchers have developed different models of E-tail brand equity, based on the traditional theory of brand equity in the off-line context.…”
Section: A Three Measures Of Off-line Brand Equitymentioning
confidence: 99%
“…Based on Keller's customer-based brand equity theory, Na et al 2005 suggested that for cyber brand equity, a similar effort is needed to find out the determinant variables -which will include the attribute, benefit and value dimensions of the brand construct. A 17 items were selected and conducted the dual, experiential and goal-oriented, motivation idea for understanding the use of internet [2].…”
Section: ) Online Researches Based On Keller's Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Na and Marshall (2005) proposed that building e-brand should include goal-oriented and experience-oriented. Goal-oriented included website interface, richness of the information, extensive information, while the experience-oriented included entertainment, society, and friendship of consumers [5]. Scholars studied e-brand from different perspectives, but they ignored the main participationconsumers.H.A.Simon pointed out that brand and the consumers' cognitive psychology have a certain connection; brand is overall feeling of consumers' cognitive processes for products and service of enterprises, it forms the unique impression for brand image.…”
Section: Introductionmentioning
confidence: 99%